2010
DOI: 10.1002/ana.21904
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, reserve, and amyloid deposition in normal aging

Abstract: ObjectiveTo determine whether amyloid deposition is associated with impaired neuropsychological (NP) performance and whether cognitive reserve (CR) modifies this association.MethodsIn 66 normal elderly controls and 17 patients with Alzheimer disease (AD), we related brain retention of Pittsburgh Compound B (PiB) to NP performance and evaluated the impact of CR using education and American National Adult Reading Test intelligence quotient as proposed proxies.ResultsWe found in the combined sample of subjects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
218
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(237 citation statements)
references
References 71 publications
13
218
2
4
Order By: Relevance
“…This [ 11 C]PIB accumulation seemed to reach a plateau at the level of dementia with moderate clinical severity (i.e., sum of the individual ratings of CDR Ͼ5) (Grimmer et al, 2009). In addition, recent studies also showed that [ 11 C]PIB uptake affected cognitive performance in normal aging Mormino et al, 2009;Rentz et al, 2010). These lines of evidence confirm that […”
Section: Similarity Index In Dmnsupporting
confidence: 69%
“…This [ 11 C]PIB accumulation seemed to reach a plateau at the level of dementia with moderate clinical severity (i.e., sum of the individual ratings of CDR Ͼ5) (Grimmer et al, 2009). In addition, recent studies also showed that [ 11 C]PIB uptake affected cognitive performance in normal aging Mormino et al, 2009;Rentz et al, 2010). These lines of evidence confirm that […”
Section: Similarity Index In Dmnsupporting
confidence: 69%
“…[3][4][5][6] Studies using amyloid PET in cognitively normal elderly individuals and individuals with mild cognitive impairment (MCI) and AD dementia have found significant relationships between cognitive deficits and increased brain fibrillar amyloid using both cross-sectional [7][8][9][10][11][12] and longitudinal data [13][14][15][16][17][18][19][20][21][22][23] ; however, other studies have not shown amyloid and cognitive correlations. [24][25][26] In autosomal dominant AD (ADAD), brain amyloid deposition is known to occur 15 years or more before the onset of clinical symptoms, 27,28 and estimated years from expected symptom onset (EYO) calculated from family history data can provide an objective biomarkerindependent estimate of an individual's relative point in the disease process.…”
mentioning
confidence: 99%
“…5 The negative impact of neuropathology on cognition is weaker among higher reserve patients, as we have shown in MS 1,4 and others have shown in aging and Alzheimer disease. 6,7 In this context, the findings of Bonnet et al 2 conflict with the cognitive reserve literature, and therefore prompted this review of their study.…”
Section: Intellectual Enrichment Lessens the Effect Of Brain Atrophy mentioning
confidence: 98%